Microwave-assisted synthesis of alkyd resins using response surface methodology - Obregón-Valencia, D.; Hadzich, A.; Bellatin, L.; Flores, S. (Elsevier, 2023)
Long alkyd resins for artistic applications were prepared by microwave synthesis of high-unsaturated vegetable oils. In this work, response surface method using split-plot optimal design was applied to optimize alkyd resin's acid value. Oil vegetable source (Sacha inchi and Linseed oil), temperature (200–240 °C), reaction time (4–12 min), and benzoic acid were evaluated as independent variables. Long alkyds resins with lower acid value considered optimal were characterized by FTIR and 1H-RMN techniques. Physicochemical properties, like color, viscosity, and drying time were assessed as well. Synthesis of alkyd resins from sacha inchi oil required less time and energy in comparison with linseed oil ones. Alkyd resins prepared with Sacha inchi oil for 210 °C and 12 min using 11.67 kJ/g at esterification stage provided a lower acid value (14 mgKOH/g), viscosity (W-X bubble Gardner), and Gardner scale color (11) in comparison with linseed oil.
Keywords: Alkyd Resins; Long Oil Alkyds; Microwave-Assisted Synthesis; Sacha Inchi Oil; Surface Response Method; Alcoholysis-Esterification; https://purl.org/pe-repo/ocde/ford#2.04.01